(3GdhLjR aj GdMbhb GdYjfjI aj VhA Gdabg GdESdGej hGdCfXeI GdSYhOjI (B=s Summary in Real Rights in the Light of Islamic Jurisprudence and Saudi system - (3HdMGL, GdYQHjs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2015)
(3hgPG GdcJGH GdehLR ddMbhb GdYjfjI, QCjJ bOQ GdeSJWGY Cf Jchf Ydi SHjd GdOQGSI GdebGQfI, hNGUI ajeG NdU Edjg abgGA GdTQjYI GdESdGejI GdZQGA, hcPG GdQLhY Edi HYV GdJTQjYGJ GdYQHjI, hGdbGfhf GdeOfj GdaQfSj, hgPG HeG jJfGSH eY GdeQMdI GdLGeYjI, aeG CMhLfG aj gPg GdMbHI Edi gPG GdfhY ef GdefgLjI GdebGQfI HGdabg GdESdGej hGdJTQjYGJ GdeOfjI GdeYGUQI, deG JKjQg ef LOd hEKQGA Ydej hCcGOjej Ydi GdUYjOjf GdfXQj hGdYedj(B.s
(3eMce YdejG(B.s
(3GdKbGaI ddJUeje hGdENQGL(B.s
(3HHdjhLQGajI (B: (3UaMI (B231-257.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3GdESdGe hGdMbhb GdYjfjIs; (3GdedcjI GdNGUI (B((3abg ESdGej(B)s; (3GdedcjIs -- (3bhGfjf hJTQjYGJs -- (3GdSYhOjIs; (3GdedcjI (B((3abg ESdGej(B)s; (3GdMbhb GdYjfjI (B((3abg ESdGej(B)s; (3GdMbhb GdYjfjIs -- (3bhGfjf hJTQjYGJs -- (3GdSYhOjIs